2014
DOI: 10.1097/bot.0b013e3182a6693f
|View full text |Cite
|
Sign up to set email alerts
|

Internal Fixation of the Distal Humerus

Abstract: Parallel locking plate configuration showed significantly higher stiffness to axial load and ultimate failure strength when compared with orthogonal locked and nonlocked plating. Locked plating configurations performed significantly better than nonlocked plating configurations, regardless of orientation. Although parallel orientation seems biomechanically superior, translation to the clinical setting may prove difficult when taking surrounding soft tissue and exposure into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…According to a finite element model of an osteoporotic bone, perpendicular and parallel dual plating of the distal humerus result in equal stability of the construct [8]. Arnander et al [1] and Caravaggi et al [22] found that 1808 plate configuration offers superior stability when compared to perpendicular plate positioning. Locking plates seem to offer higher stability of the osteosynthesis in comparison to nonlocking plates [22].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to a finite element model of an osteoporotic bone, perpendicular and parallel dual plating of the distal humerus result in equal stability of the construct [8]. Arnander et al [1] and Caravaggi et al [22] found that 1808 plate configuration offers superior stability when compared to perpendicular plate positioning. Locking plates seem to offer higher stability of the osteosynthesis in comparison to nonlocking plates [22].…”
Section: Discussionmentioning
confidence: 98%
“…Arnander et al [1] and Caravaggi et al [22] found that 1808 plate configuration offers superior stability when compared to perpendicular plate positioning. Locking plates seem to offer higher stability of the osteosynthesis in comparison to nonlocking plates [22]. While some biomechanical evidence points to the conclusion that 1808 positioning of the distal humerus plates might be preferred over 908 positioning [1,22], equal clinical results of both fixation techniques have been reported [15,23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current gold standard for surgical treatment of intra-articular distal humeral fractures is open reduction and internal fixation with plates and/or screws [3]. In earlier studies, locked plating configurations demonstrated significantly better performance than nonlocked plating configurations, independently of their orientation [4]. The fixation methods evolved into the present third generation of locking plates which include anatomical plate design and poly-axial locking screws.…”
Section: Introductionmentioning
confidence: 99%
“…exposure of the distal humerus must be taken into consideration [4]. Hence, under some circumstances the 90°angle configuration might be preferable.…”
Section: Introductionmentioning
confidence: 99%